A Proposed Method for Specifying Effect the Dynamic of Critical Path in Delays Analysis - جراد, فايز (Latakia University Journal -Engineering Sciences Series, 2021)
The use of Critical Path Method (CPM) has become an accepted standard in all major construction works. The boards and courts have a willingness to use network analysis techniques to identify delays and disruptions and their causes. The critical path must be kept current to reflect delays and frequently changes during the course of project. Many methods used CPM in delay analysis, some of which are based on final as-built critical path such as net working duration method. Other methods tried to reflect the changes in critical path periodically during project implementation such as window analysis, snapshot, time impact technique, and isolated delay type method. The reliability of results, in these methods, is a function of the number of periods used through analysis. These methods do not reflect the realistic changes in critical path during project progress. In this paper, a proposed method, which reflects the dynamic changes in the critical path(s) during the course of project, is presented. Updating the as-planned schedule on an activity-by-activity (i.e. after the finish of changed activities) basis can realistically prove the dynamic nature of critical path. Delays and other changes are considered in the analysis and then the changes in critical path and project deadline is tested. The proposed method offers both the owner and contractor a clear knowledge about the effect of delays of each activity on the succeeding activities as well as project completion date. On the other hand, the analysis can be performed after the project finish retrospectively. An illustrative example problem is presented to implement the proposed method.